Studi Komparasi Taman Kota Lumintang Dan Taman Kota Puputan Margarana Niti Mandala Renon Sebagai Sarana Leisure And Recreation - Permatasari, Shindi Ayu; Mahagangga, I Gusti Agung Oka (JURNAL DESTINASI PARIWISATA; Vol 6 No 2 (2018): VOL 6, NO 2 (2018): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2018.v06.i02.p06, 2019)
Lumintang City Park is located at Mulawarman Street, Lumintang, Dauh Puri Kaja, North Denpasar, while Renon City Park is located in Niti Mandala, Denpasar, Renon. Renon City Park Located in the middle of Denpasar City. Both places are in the same area, and not far from the city center. Both parks are very crowded visitors to do leisure and recreation activities. The method used to find the data is observation, interview, and questionnaire. The method used to determine the sample is quota sampling and accidental sampling. Methods for analyze data is comparative analysis and descriptive statistical analysis. The purpose of this research was to know the comparison between Lumintang city Park and Renon City Park as a place of leisure and recreation. The result of comparison with the first aspect is he leisure equation as a activities and the mood / positive mental, the difference is in the number of visitors. the second is recreation equations visitors a lot to relax at the day, the difference is in the number of respondents. The third aspect is physical motivations the equaptions is for sports, the difference is the number of respondents. The fourth aspect is facilities include sports equipment and children playground, the equation good management, the difference is the number of respondents. The equation is a good parking area management and the differences is in the number of respondents and the equaptions is a  good toilet management and the difference in the number of respondents. The similarity is there is no management for the trash can, the difference is in Lumintang city park many respondents said not good while in Renon city Park many respondents stated good. And the last management of the park bench the equation does not exist whereas the difference is in Lumintang city park many respondents stated good and in Renon City Park many respondents stated not good. The fifth aspect is visitor aspect of the equation there are many female visitors, the difference is number of respondents. The age aspect the equation is age of visitors is 16-25 years old, the difference is the number of respondents. Equality in employment is public servant, the difference is number of respondents. For the origin of the region there is no similarity and the difference is in Lumintang City Park many visitors that comes from Denpasar while in Renon City Park many visitors from the outside Denpasar. Keywords : comparison, leisure, recreatio n, lumintang city park, niti mandala renon city park